Characteristics of Soils Developing from Gabbro, Phyllite and Chert Parent Rock in Karangsambung District - Ratna Taher; Makruf Nurudin; Eko Hanudin (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2019)
Understanding the nature of the soil is very important to know the potential and the proper management of the soil. This study aimed to determine the differences in morphological, physical, and chemical properties of the soils developing from gabbro, phylitte and chert parent materials. The soil profile was made to represent each parent rock of gabbro, phyllite and chert located on the upper and middle slopes with pine-dominated vegetation and mixed gardens. Observation in the field is a professional description to observe soil morphology. Soil samples were taken at each horizon to analyze soil physical properties (bulk density, particle density, and texture), soil chemical properties (pH, exchanged cations, cation exchange capacity, available P, organic C, and total N). Texture analysis results showed that clay content of the soil developing from parent rock of Gabro 1 is the highest, followed by the soil clay content from Chert 1, Phyllite 1, Chert 2, Phyllite 2, and Gabbro 2, respectively. The order of soil acidity level (pH) is Gabbro 2 > Gabbro 1> Chert 1 Chert 2 > Phyllite 1 Phyllite 2. Meanwhile, the order of the cation exchange capacity is Gabbro 1> Gabbro 2> Phyllite 1> Chert 1> Phyllite 2> Chert 2, and the order of the base saturation is Chert 2> Gabbro 2> Chert 1> Phyllite 2 > Phyllite1> Gabbro 1.